2014
DOI: 10.1038/jid.2014.174
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Cell Death with Antigen Deposition in Skin Enhances Vaccine Immunogenicity

Abstract: Vaccines delivered to the skin by microneedles – with and without adjuvants – have increased immunogenicity with lower doses than standard vaccine delivery techniques such as intramuscular (i.m.) or intradermal (i.d.) injection. However, the mechanisms behind this skin-mediated ‘adjuvant’ effect are not clear. Here, we show that the dynamic application of a microprojection array (the Nanopatch) to skin generates localized transient stresses invoking cell death around each projection. Nanopatch application caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
119
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(130 citation statements)
references
References 53 publications
10
119
1
Order By: Relevance
“…However, skin immunization has not been broadly adopted to date, due to lack of safe adjuvants and technical difficulties in injecting vaccines into the ultrathin (<2 mm) skin tissue (3,4). We have demonstrated that controllable skin injury can serve as safe "adjuvant" for cutaneous vaccination and similar observations have been also made by other investigators (5)(6)(7). Treatment of the inoculation site with nonablative fractional laser (NAFL) generates an array of microthermal zones (MTZs) beneath the stratum corneum (8).…”
supporting
confidence: 77%
“…However, skin immunization has not been broadly adopted to date, due to lack of safe adjuvants and technical difficulties in injecting vaccines into the ultrathin (<2 mm) skin tissue (3,4). We have demonstrated that controllable skin injury can serve as safe "adjuvant" for cutaneous vaccination and similar observations have been also made by other investigators (5)(6)(7). Treatment of the inoculation site with nonablative fractional laser (NAFL) generates an array of microthermal zones (MTZs) beneath the stratum corneum (8).…”
supporting
confidence: 77%
“…This finding correlated well with the results presented in this doctoral thesis [344]. Cell death resulting from ballistic delivery of micro-particles to the skin was recently reported [242].…”
Section: Adjuvants and Cell Deathsupporting
confidence: 91%
“…(Figure 4.5), and more antigen co-localised with dead cells following NP than i.d. immunisations (Figure 7.4) [344]. However, it was not clear whether co-localisation of antigen with dead cells interspersed with live cells was essential for enhanced antibody production.…”
Section: Co-localising Nanopatch™-mediated Cell Death Adjacent Live mentioning
confidence: 99%
See 2 more Smart Citations